Tsunamis from source to coast - Wronna, Martin (2022)
Tsunami disasters pose a significant threat to coastal communities. In the last decades, tsunamis caused enormous destruction and exceeding 250000 fatalities. International efforts led to sig-nificant advances in tsunami science and research, but recent events demonstrated some limi-tations. Thus, it is essential to increase our knowledge of the source to coast tsunami phenom-enon. A better understanding of potential tectonic structures and other generation mechanisms is needed, especially in complex geologic domains or where sources are unknown. Furthermore, we need to improve Tsunami Warning Systems (TWSs) to provide timely alerts for communi-ties in the near field. Therefore, potential tsunamigenic sources in the diffuse plate boundary setting and the near field of the southwest Iberian margin (SWIM) are investigated. For the March 31, 1761, trans-atlantic tsunami, numerical modelling has been used to propose a structure that agrees with tsunami travel times, tsunami observations, macroseismic data, and kinematic plate modelling. Since there exists a description of a tsunami for the November 11, 1858, Sétubal earthquake, its source has been investigated using macroseismic analysis. The analysis suggests a local structure in a compressive regime with weak to moderate tsunamigenic potential. Future tsu-nami hazard assessments need to include the sources of the investigated events. To quickly estimate the tsunami impact, the Tsunami Runup Predictor (TRP), an empirical source-to-coast method to instantly provide first-order estimates of the tsunami runup based on waveform parameters has been developed. The TRP is helpful for emergency managers and evacuation planning for near-field events. Moreover, the author of this thesis contributed to the tsunami impact assessment of September 28, 2018, Palu tsunami, where tsunamis generated by multiple sources caused runup heights up to 9.2 m. However, for local sources, tsunami warning remains challenging; thus, communities need to be prepared how to respond appropriately to earthquakes and tsunamis with or without warning.